A Review of Operational Research Applications in Medical Waste Collection from 2010 to 2022 - ALGHAMDI, RAWA (2022)
Medical waste is one of the most hazardous types of waste because it contains numerous harmful bacteria. Therefore, improper collection and disposal practices can constitute a significant threat to the environment and human health, particularly in developing countries. Decision-makers can improve waste recovery and save a considerable amount of money by using computerised systems built on operational research (OR) principles. Indeed, when assisted by these systems, decision-makers have improved their critical thinking skills and creativeness, leading to better overall control of medical waste management. The importance of OR applications is well recognised in the literature, but there has been no review of the published research on medical waste collection focused on the impact of the pandemic. The aims of this paper are as follows: (1) to conduct a systematic review of OR applications in medical waste collection during the period 2010–2022, (2) to highlight the applications of OR optimisation models in medical waste management, (3) to identify the differences between regular waste and medical waste, (4) to determine the impact of COVID-19 on implementing medical waste collection practices and (5) to draw attention to the gap in the literature and identify promising areas for future studies. The results determine the main characteristics of the OR models in medical waste collection. The objective functions, constraints, solution methods and geographic locations of case studies are discussed. With the goal of providing a solid foundation for subsequent OR investigations of medical waste collection and disposal procedures, the results provide recommendations for future research directions within the context of extensions to current models to fill the gap identified in the literature. The recommendations can also help improve waste management in the event of another pandemic. Because they will aid the establishment of long-term adjustments to medical waste management, the recommendations will also contribute to improvements in the management of COVID-19 waste.